2017
DOI: 10.5005/jp-journals-10053-0053
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Tooth in the Anterior Wall of Maxillary Sinus

Abstract: A 16-year-old male patient reported to our department with a chief complaint of pain and swelling in the upper left cheek region. On examination, a maxillary canine was found ectopically in the anterior wall of maxillary sinus. Ectopic eruption of teeth into regions other than the oral cavity is rare. We present one such case of ectopic eruption of maxillary canine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The presence of teeth in the maxillary sinus is a rare finding, and it is found accidentally on radiographic examination. 2 Radiograph examination in this case showed that the ectopic canine tooth was in the anterior wall of the right maxillary sinus. The presence of teeth in the maxillary sinus will cause an inflammatory reaction in the sinus and cause local sinonasal symptoms like nasal obstruction, facial fullness, headache, hyposmia, and recurrent chronic sinusitis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The presence of teeth in the maxillary sinus is a rare finding, and it is found accidentally on radiographic examination. 2 Radiograph examination in this case showed that the ectopic canine tooth was in the anterior wall of the right maxillary sinus. The presence of teeth in the maxillary sinus will cause an inflammatory reaction in the sinus and cause local sinonasal symptoms like nasal obstruction, facial fullness, headache, hyposmia, and recurrent chronic sinusitis.…”
Section: Discussionmentioning
confidence: 61%
“…1 The tooth may be displaced into sinus due to trauma resulting in the displacement tooth bud, infection, crowding, or genetic factors. 2 The presence of teeth in the maxillary sinus will cause an inflammatory reaction in the sinus and cause local sinonasal symptoms like nasal obstruction, facial fullness, headache, hyposmia, and recurrent chronic sinusitis. Other rare symptoms include epistaxis, fever, rhinorrhea, nasolacrimal duct obstruction and a deviation of the nasomaxillary anatomy.…”
Section: Introductionmentioning
confidence: 99%